(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Manju Kapur is a feminist writer because in all her novels she deals with the pathetic and oppressive situations of Indian women. Her novels denounce the socio-cultural predicament of Indian women imprisoned in a male-dominated patriarchal society. Her main novels are Difficult Daughters, A Married Woman, Homes, The Immigrant, and Custody. Most of her main characters are educated wives and belong to the Indian middle class. They face struggles for freedom, identity, equality with people, and their own space. Her suffering and suffocation in her family and marital relationships are clearly reflected in her novels. This paper examines Manju Kapur's a Married Woman from a feminist perspective.